OP0165 Changes in Lipoprotein(A) after Treatment with Tocilizumab (TCZ), Adalimumab (ADA), and Methotrexate (MTX) in Patients with Rheumatoid Arthritis (RA). (10th June 2014) - Gabay, C.; McInnes, I.; Kavanaugh, A.; Tuckwell, K.; Collinson, N.; Klearman, M.; Green, J.; Sattar, N.
Abstract : Background: Clinical and epidemiological evidence implicates elevated lipoprotein (a) [Lp(a)] level as a risk factor for cardiovascular disease (CVD). 1 Lp(a) is also implicated as a causal agent in the atherothrombotic process. 1 RA pts are at increased risk for CVD and have higher Lp(a) levels than the general population. 2 Treatment guidelines recommend reduction of Lp(a) at levels >50 mg/dL. 3 Niacin is the most recognized means to lower Lp(a) but is no longer recommended given recent trial results. 4 Although some evidence implies a beneficial role for TNF inhibitors in reducing CV risk and mortality in RA pts, their effect on Lp(a) remains unclear. Some studies report a decrease in Lp(a) following treatment with MTX and TNF inhibitors; others show no such effects. 5–7 Interleukin-6 (IL-6), a proinflammatory cytokine, has been shown to increase Lp(a) levels in monkey hepatocyte cultures. 8 Conversely, inhibition of IL-6 signaling with TCZ decreases serum Lp(a) levels. 9, 10 Objectives: This post hoc analysis examined the response of Lp(a) to TCZ in comparison to ADA and to MTX in two separate clinical trials. Methods: ADACTA was a randomized, double-blind, phase 4 study in RA pts (TCZ, n=163; ADA, n=163). 11 Pts received TCZ 8 mg/kg IV Q4W or ADA 40 mg SC Q2W for 24 wks, both as monotherapy. MEASURE was a randomized, double-blind, phase 3 study in RA pts (TCZ + MTX, n=69; pbo + MTX, n=63). 10 Pts received TCZ 8 mg/kg IV Q4W or pbo IV Q4W, both in combination with MTX. Serum samples were analyzed at baseline (BL) and wk 8 for Lp(a). Change from BL to wk 8 in Lp(a) was summarized within each study split by EULAR and ACR50 response at wk 24. Shifts from >50 mg/dL to ≤50 mg/dL in Lp(a) from BL to wk 8 were summarized for each study. Results: A greater reduction in Lp(a) was seen in pts receiving TCZ compared to those receiving ADA ( p <0.0001) and in pts receiving TCZ + MTX compared to those receiving MTX ( p <0.0001) (Table 1 ). Although the reduction was greater in both ACR50 and EULAR responders compared to nonresponders, the numerical differences were mostly small. At wk 8, numerically higher proportions of pts with BL Lp(a) >50 mg/dL improved (defined as achieving Lp(a) ≤50 mg/dL) in the TCZ group (11/21 [52.4%]) compared to the ADA group (6/24 [25%]) and in the TCZ + MTX group (7/12 [58.3%]) compared to the MTX group (2/20 [10%]). Conclusions: The current analysis showed greater reduction of Lp(a) levels in RA pts treated with TCZ monotherapy compared to ADA and with TCZ + MTX compared to MTX. This effect appears to be partially related to treatment response. These results suggest that IL-6 receptor inhibition may modulate Lp(a) more than MTX or TNF blockade with ADA. More studies are needed to elucidate the hierarchy of signaling pathways that modulate Lp(a) and how this may impact CV risk. References: Curr Atheroscler Rep 2013;15:360. Circulation 2003;108:2957. Eur Heart J 2010;31:2844. N Engl J Med 2011;365:2255. Ann NY Acad Sci 2006;1069:414. Arthritis Rheum 2007;56:831. Clin Exp Rheum 2013;31:415-21. Arterioscler Thromb Vasc Biol 1998;18:984. PLoS One 2010;5:e14328. Ann Rheum Dis 2013 doi:10.1136. Lancet 2013;381:1541. Disclosure of Interest: C. Gabay Grant/research support: Roche, AbbVie, Merck, Consultant for: Roche, AbbVie, Merck, I. McInnes Grant/research support: Pfizer, Roche, Consultant for: BMS, Pfizer, NovoNordisk, AstraZeneca, Eli Lilly, UCB, Speakers bureau: BMS, Pfizer, NovoNordisk, AstraZeneca, Eli Lilly, UCB, A. Kavanaugh Grant/research support: Roche/Genentech, K. Tuckwell Employee of: Roche, N. Collinson Employee of: Roche, M. Klearman Shareholder of: Roche/Genentech, Employee of: Roche/Genentech, J. Green Employee of: Roche, N. Sattar Consultant for: Roche, Speakers bureau: Roche DOI: 10.1136/annrheumdis-2014-eular.3030